Enhancing Traditional Health Services: Empowering Holistic Care Clinic - Sri Mukhodim Faridah Hanum; Hesty Widowati; Mochammad Rizal Yulianto; Lidia Agustin Tjondro I (Universitas Muhammadiyah Sidoarjo, 2023)
Traditional Health Service Development: Enhancing Knowledge and Skills for Holistic Care Clinic. This study aims to improve the knowledge and skills of Pimpinan Cabang Aisyiyah (PCA) Jambangan Surabaya members in providing traditional health services at Klinik Aisyiyah Holistic Care. The program includes training in acupressure and marketing and financial management. Twelve participants from PCA Jambangan attended the training and registered with the Indonesian Association of Acupressure Practitioners (P3AI) to undergo competency tests and obtain necessary permits from the Surabaya Health Department for practicing traditional health services at the clinic. The implementation coincided with the PCA Jambangan's musycab launching. The successful completion of the program resulted in the issuance of the clinic's operational permit and the availability of qualified human resources to provide complementary health services to the community. Highlight: Empowering traditional health practitioners: The study focuses on enhancing the knowledge and skills of PCA Jambangan members to provide effective traditional health services at Klinik Aisyiyah Holistic Care. Training in complementary therapies: The program includes specialized training in acupressure, enabling participants to offer holistic care options to the community. Obtaining necessary permits: Participants undergo competency tests and secure permits from the Surabaya Health Department, ensuring legal practice of traditional health services at the clinic. Keyword: Traditional Health Services, Holistic Care Clinic, Knowledge Enhancement, Skills Development, Acupressure Training